A comprehensive meta-analysis of cognitive-behavioral interventions for social anxiety disorder in children and adolescents. (August 2016) - Scaini, Simona; Belotti, Raffaella; Ogliari, Anna; Battaglia, Marco
Highlights: Meta-analysis was conducted on CBT trials for Social Anxiety in childhood. The study assessed Effect Size in three designs: pre-post, between group, follow-up. Results support the effectiveness of CBT for Social Anxiety. A significant moderating effect was found for the variable "number of treatment sessions". Including Social Skills Training may further enhance the impact of treatment. Abstract: The effectiveness of different types of CBT for children and adolescents suffering from Social Anxiety Disorder (SAD) is generally supported. However, no systematic efforts have been made to quantitatively summarize and analyse the impact of specific variables on therapeutic outcome. Here, we assessed the magnitude and duration of CBT effectiveness in children and adolescents with SAD. The effectiveness of CBT was supported by the effect sizes of studies that had examined pre-post (g = 0.99), between-group (g = 0.71), and follow-up responses (follow-up vs. pre-test mean g = 1.18, follow-up vs. post-test mean g = 0.25). A significant moderating effect was found for the variable "number of treatment sessions". In addition, larger effect sizes were found in studies that included "Social Skills Training" sessions in the intervention package. Data support the effectiveness of CBT interventions and its durability for SAD in children and adolescents. Adding social skills training to the intervention package can further enhance the impact of treatment.